2008
DOI: 10.1038/oby.2007.48
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Eating Attitudes and Behaviors in Overweight Youth

Abstract: Disordered eating attitudes and behaviors appear to be quite common in youth, and overweight youth have been identified as a subset of the population at particularly high risk for endorsing such symptoms. Overweight and eating disorder (ED) symptomatology independently confer significant threats to one's physical and psychosocial health, showing strong links with body weight gain and risk for ED development. When concurrent, the risk for negative health outcomes may be compounded. The purpose of this article i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
143
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(160 citation statements)
references
References 128 publications
9
143
0
7
Order By: Relevance
“…En la relación severidad de la obesidad y riesgo de un TCA, encontramos, a diferencia de lo publicado en la literatura [34][35][36][37][38][39] , sólo una tendencia a ser mayor en los pacientes más obesos. Pero, lo que si se observó fue que los adolescentes con mayor severidad de su obesidad presentan puntajes más altos del test EDI-2, lo que indica una mayor sintomatología de riesgo de trastornos alimentarios.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En la relación severidad de la obesidad y riesgo de un TCA, encontramos, a diferencia de lo publicado en la literatura [34][35][36][37][38][39] , sólo una tendencia a ser mayor en los pacientes más obesos. Pero, lo que si se observó fue que los adolescentes con mayor severidad de su obesidad presentan puntajes más altos del test EDI-2, lo que indica una mayor sintomatología de riesgo de trastornos alimentarios.…”
Section: Discussionunclassified
“…Por otro lado, los adolescentes muestran un aumento de los trastornos de la conducta alimentaria (TCA) 4 . Ambas patologías constituyen problemas de salud pública complejos y prevalentes que requieren ser abordados [5][6][7][8][9] .…”
unclassified
“…Of the included 3248 respondents, whose mean age was 14.83 (SD = 1.28), 1608 (49.5%) were males and 1640 (50.5%) were females. Respectively there were 758, 781, 916, 792 participants from Year 7,8,9,10. This study extracted responses to the 11 questions directly related to body image.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Now when more and more people think that person is beautiful, attractive and healthy only if he/she is slender and being fat is considered abominable causing fear of becoming overweight, adolescents begin to think that normal puberty is uniform with loss of weight control -in their view teenagers with normal feminine/ masculine body shape are obese, ugly, lazy loser's incapable of self-control. Body dissatisfaction leads to negative health consequences, increased risk of obesity and usage of inappropriate methods of weight control [8].…”
mentioning
confidence: 99%
“…23 In the present study there was no association found between the risk of anorexia nervosa and the selected demographic variables, whereas another study revealed that the presence of overweight preoccupation and fear of fatness in adolescents is strongly associated with an increased risk of developing clinical eating disorders. 24 The study was conducted on a smaller number of samples where the results cannot be generalized, which is the limitation of the study.…”
Section: Consistent Withmentioning
confidence: 99%